Design of thermochromic polymer blends containing low-mass compounds - Kuhakongkiat, N; Sugiyama, M; Guesnier, M; Azaman, FA; Yoshida, K; Yamaguchi, M (Wiley, 2024)
We investigated the light transmittance of an immiscible polymer blend comprising a copolymer of ethylene and vinyl acetate (EVA) and a terpolymer of vinyl butyral, vinyl alcohol, and vinyl acetate (PVB). Both EVA and PVB are used in the interlayers of laminated glass. We found that the transparency of the blend depends on the ambient temperature. This can be attributed to the difference in the temperature dependence of the refractive index between EVA and PVB. The blend has good transparency at room temperature because the difference between the refractive indices of its components is minimal. At high or low temperatures, however, the blend becomes opaque owing to light scattering. The addition of a plasticizer favorably affects the temperature range over which the blend exhibits high transparency, because the refractive index and its temperature dependence are affected by the plasticizer. We also evaluated the interphase transfer of a plasticizer between EVA and PVB at various temperatures. (C) 2017 Wiley Periodicals, Inc.